Madrasta ([Quezon City] Star Citnema)
Not all stepmothers are wicked witches. In fact, many of them are like Mariel, a loving, caring individaul who tries to belong in a family which she is not part of, which cannot be truly hers.
VCD
Sharon Cuneta, Christopher De Leon, Zsazsa Padila, Nida Blanca, Claudine Barreto.
Keywords: Mothers; Family--Phils.; Feature films